The role of social studies curricula in developing 21st century skills from the point of view of teachers of the first cycle of the basic education stage (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of the current research is to identify the role of social studies curricula in developing twenty-first century skills from the point of view of teachers of the first cycle of the basic education stage. The researcher adopted the descriptive analytical approach, and designed a list of twenty-first century skills, and a questionnaire consisting of (50) phrases, and the research included sample of class teachers, it consisted of (145) teachers, and the following results were reached: The degree of development of social studies curricula for twenty-first century skills in general was (3.01), which is medium grade; As for the role of the curriculum according to each axis: in the first rank with a medium degree, the life and profession axis, learning and creativity in the second rank with a medium degree, and the digital culture axis in the third rank with a weak degree There are statistically significant differences between the averages of teachers' answers to the twenty-first century skills questionnaire according to the educational qualification variable in favor of diploma holders and above, and according to the variable years of experience, in favor of the experience of 10 years and above.
Keywords: Curricula; Social Studies-21st Century Skills; First Cycle; Basic Education Stage